Improvement of transitional care from hospital to home for older patients, the TIGER study: protocol of a randomised controlled trial. Issue 2 (8th February 2021) - Rimmele, Martina; Wirth, Jenny; Britting, Sabine; Gehr, Thomas; Hermann, Margit; van den Heuvel, Dirk; Kestler, Andreas; Koch, Thomas; Schoeffski, Oliver; Volkert, Dorothee; Wingenfeld, Klaus; Wurm, Susanne; et al.
Abstract : Introduction: In Germany, an efficient and feasible transition from hospital to home for older patients, ensuring continuous care across healthcare settings, has not yet been applied and evaluated. Based on the transitional care model (TCM), this study aims to reduce preventable readmissions of patients ≥75 years of age with a transitional care intervention performed by geriatric-experienced care professionals. The study investigates whether the intervention ensures continuous care during transition and stabilises the care situation of patients at home. Methods and analyses: Randomised controlled clinical trial, recruiting between 25 April 2018 and 31 December 2019 in one German hospital in the city of Regensburg. The intervention group is supported by care professionals in the transition process from hospital to home for up to 12 months. Based on TCM, the intervention includes an individual care plan according to a patient's symptoms, risks, needs and values. The plan is advanced in the domestic situation via personal visits and telephone contacts. All necessary care actions regarding, for example, mobility, residence adjustments, or nutrition, are initiated to be executed by ambulant care services, and are monitored, evaluated and adapted if necessary. In supervising the care plan, the care professionals do not administer active care services themselves but coordinate them. Patients and their caregivers are actively engaged in the care planning and execution. In contrast, the control group receives only usual discharge planning in the hospital and usual ambulatory care. The primary outcome is the all-cause readmission rate assessed using health insurance data within a follow-up of up to 12 months after hospital discharge. Secondary outcomes include care quality, mobility, nutritional and wound situation, and health-related quality of life. They are assessed at baseline, after 1 month, 3 months, 6 months, and at the end of study visit. Additionally, the economic efficiency of the intervention will be evaluated. Ethics and dissemination: Ethics approval for the trial was obtained from the Ethics Committee of the Friedrich-Alexander-Universität Erlangen-Nürnberg. Results will be published in peer-reviewed, open-access scientific journals and disseminated at national and international research conferences and through public presentations in the geriatric and healthcare community. Trial registration: ClinicalTrials.gov identifier: NCT03513159 .